Pre-hire factors and workplace ethnic segregation - Magnus Strömgren; Tiit Tammaru; Maarten van Ham; Szymon Marcinczak; Olof Stjernström; Urban Lindgren (Institute for the Study of Labor (IZA), 2011)
In addition to neighbourhoods of residence, family and places of work play important roles in producing and reproducing ethnic segregation. Therefore, recent research on ethnic segregation and contact is increasingly turning its attention from residential areas towards other important domains of daily interethnic contact. The key innovation of this paper is to clarify the role of immigrants' pre-hire exposure to natives in the residence, workplace and family domains in immigrant exposure to natives in their current workplace. The study is based on Swedish population register data. The results show that at the macro level, workplace neighbourhood segregation is lower than residential neighbourhood segregation. Our micro-level analysis further shows that high levels of residential exposure of immigrants to natives help to reduce ethnic segregation at the level of workplace establishments as well.
urn:nbn:de:101:1-201104134258
Keywords: J15; J61; R23; 330; neighbourhood effects; residential segregation; workplace segregation; intermarriage; longitudinal analysis; Sweden; Segregation; Arbeitsplatz; Wohnstandort; Bevölkerung; Ethnische Beziehungen; Ehe; Schweden